A sustainable software testing process for the Square Kilometre Array project. Issue 1 (30th September 2020) - Brajnik, Giorgio; Bartolini, Marco; Rees, Nicholas
Abstract: In this paper we show how to achieve a sustainable software testing process in a very complex scientific project, the Square Kilometre Array (SKA) radio observatory. The project currently involves 13 countries, 16 agile development teams of about 150 individuals, governed through the Scalable Agile Framework (SAFe) framework; the software that is being built ranges from user interfaces to control systems, from transactional applications to high performance parallel scientific processing code. The paper illustrates the testing challenges we have to tackle; it also defines what a "sustainable testing process" is and how that constitutes the foundation of an incremental adoption plan rooted on systems thinking. The plan is then described, highlighting the principles we adhered to for synthesising a sequence of 9 basic testing goals that are currently being rolled out. We are confident that similar decisions can be made on many large scientific projects that are developed with agile methods.